Niepokalane Poczęcie Najświętszej Marii Panny w myśli św. Bernarda z Clairvaux .......... 157 - Chojnacki, Marek Piotr (Dzieje i kultura Cystersów w Polsce, 2025)
IMMACULATE CONCEPTION BLESSED VIRGIN MARY IN THE THOUGHT OF ST. BERNARD OF CLAIRVAUXSt. Bernard of Clairvaux, a representative of the so-called monastic theology, is considered a representative of medieval Mariology in the period preceding the development of scholasticism. His predilection for Marian cult, however, did not allow him to recognize the Immaculate Conception, even in the form of the liturgical feast of the Conception of the Blessed Virgin Mary. This was because he wanted to be faithful to the messages of the Church Fathers and did not see the need to establish an additional holiday. The actual source of this belief is inherited from St. Augustine, the anthropology of St. Bernard. Original sin accompanies man from the moment of conception, so Mary could not have been conceived immaculately. However, she was purified in her mother’s womb and was born free from original sin. This short article also presents quotations from the writings of St. Bernard, which authorizes such an understanding of the holy abbot’s work.